Price Points and Price Dynamics - Volker Hahn; Michal Marencak (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper proposes a macroeconomic model with positive trend inflation that involves an important role for price points as well as sticky information. We argue that, in particular, a variant of our model that allows for a general distribution of price points is more successful in explaining several stylized facts of individual price setting than a benchmark model that is based on Calvo price-setting. More specifically, it makes empirically reasonable predictions with regard to the duration of price spells, the sizes of price increases and decreases, the shape of the hazard function, the fraction of price changes that are price increases, and the relationship between price changes and inflation. Moreover, our model implies plausible aggregate effects of monetary policy in contrast with a model with a prominent role for price points but no information rigidities.
Keywords: E31; E37; 330; price stickiness; price point; sticky information